2013
DOI: 10.1021/es304780a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polyparameter Linear Free Energy Relationship (pp-LFER) Substance Descriptors for Established and Alternative Flame Retardants

Abstract: Polyparameter linear free energy relationships (pp-LFERs) can predict partition coefficients for a multitude of environmental and biological phases with high accuracy. In this work, the pp-LFER substance descriptors of 40 established and alternative flame retardants (e.g., polybrominated diphenyl ethers, hexabromocyclododecane, bromobenzenes, trialkyl phosphates) were determined experimentally. In total, 251 data for gas-chromatographic (GC) retention times and liquid/liquid partition coefficients (K) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…Furthermore, hydrophobic chemicals tend to bind to sediment OC, leading to low C free and C s,bioavailable ( Table 1). As shown in Supplemental Data, Table S1, BCFs were estimated from C b,lipid and C free , and they were comparable to the values of less brominated PBDEs in the literature [26]. The relationship of log BCF (estimated) ¼ 0.95 Â log BCF (literature) (r 2 ¼ 0.81) suggested that C free was a good metric for the bioavailability of BFRs in sediment.…”
Section: Bioaccumulation Kinetics and Chemical Hydrophobicitysupporting
confidence: 68%
See 2 more Smart Citations
“…Furthermore, hydrophobic chemicals tend to bind to sediment OC, leading to low C free and C s,bioavailable ( Table 1). As shown in Supplemental Data, Table S1, BCFs were estimated from C b,lipid and C free , and they were comparable to the values of less brominated PBDEs in the literature [26]. The relationship of log BCF (estimated) ¼ 0.95 Â log BCF (literature) (r 2 ¼ 0.81) suggested that C free was a good metric for the bioavailability of BFRs in sediment.…”
Section: Bioaccumulation Kinetics and Chemical Hydrophobicitysupporting
confidence: 68%
“…Polybrominated diphenyl ether (PBDE) and decabromodiphenyl ethane (DBDPE) in sediment collected from an electronic waste recycling site in South China [6], and the K OW value of DBDPE was from Kierkegaard et al [14]. The C free was calculated by dividing C fiber by the fiber-water partition coefficient (K fw ), which was calculated from log K OW using the equation of Stenzel et al [26]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partitioning systems that involve water as one of the phases are even a requirement for accurate determination of B. 47 However, experimental determination of solvent−water partition coefficients needs intensive laboratory work, and the results are typically less accurate and less precise compared to chromatographic retention times. We can thus generally conclude that a combination of methods is the most efficient way to obtain a robust set of descriptors.…”
Section: ■ General Description Of Pp-lfer Modelsmentioning
confidence: 99%
“…2 A similar trend was found for B of aliphatic 43 The choice of B or B 0 has not become a major issue to date, at least in environmentally related studies, because the number of chemicals that need B 0 is small, and the reported differences between B and B 0 are also relatively small (<0.2). 14 Recently, Stenzel et al 47 found that different B values have to be used to characterize the partitioning into water and into trifluoroethanol for some flame retardants such as polybrominated diphenyl ethers and phosphate triesters 47 (Table S1 in the Supporting Information (SI)). B for the water phase are generally higher than B for the trifluoroethanol phase, and differences are up to 0.6, which can cause a difference of >2 log units in predicted solvent or sorbent−water partition coefficients.…”
Section: ■ Solute Descriptors: Further Considerationsmentioning
confidence: 99%